Efecto De La Fertilizacion Fosforo Azufrada Sobre El Sistema Radical Y El Rendimiento De Soja En El Centro De Argentina - M. D. Bongiovanni; G. A. Cerioni; A. Gonzalez Giorgi; E. Dobla (European Scientific Journal, ESJ, 2016)
The objective was to evaluate grain the effect of sulfur and phosphorus fertilization on root growth, nodules and soybean yield. The test was performed at 25 km west of Coronel Baigorria department Río Cuarto; Córdoba, Argentina on a Haplustol entic from the series Alpa Corral. Treatments applied were made different doses of single superphosphate (21% P205 y 12% de S).TO: control treatment, no fertilizerT1: 5,5 Kg ha-1de P y 7,2 Kg ha-1de S; T2: 10,9 Kg ha-1de P y 14,4 Kg ha-1 de S y T3: 16,48 Kg ha-1 de P y 21 Kg ha-1.During crop cycle the following observations and measurements: emerged seedlings, root dry weight, number of nodules, primary root diameter, root length density (DLR), and determine harvest, crop yield (kg/ha) and levels of available soil phosphorus at harvest. In this research project the application of phosphorus-sulfur fertilizer produced changes in soybean root system, by increasing dry weight of roots, generating lateral growth, improving the symbiosis with nitrogen-fixing bacteria which result in more number of nodules per root. Fertilization also modified rooting patterns increasing DLR in most fertilizer treatments, effects that resulted in an increase in soybeans yield.